(untitled) (Revista Cientifica Ingenio Magno, 2022)
This document aims to provide the reader with information about the Des and 3Des Encryption algorithms, this through research in different sources of scientific certification data referenced in the document. Currently, the usability of these algorithms is not frequent due to obsolescence, but without a doubt they were the basis for other more robust encryption algorithms that provide more reliability and security for the end user today. This document seeks a critical and argued view for the reader’s knowledge of the subject based on research carried out by the authors of the document, for this it is necessary to make known the importance of encryption algorithms and the usability that they have today in day.